Analysis of periodical use at the U.P. Medical Library a study of the use patterns of the periodical literature in medicine - Dizon, Julio Jr. E. (1982)
An evaluation of the extent of use of the periodical collection of the UP Medical Library was conducted during the first semester of academic year 1981-1982. The objectives of the study are: 1) to identify the journal titles that are most heavily used, and 2) to determine the years in the life of the journals which provide much of the information sought by the users. Three concomitant hypotheses were formulated in studying the patterns of use of medical periodical literature. These are: 1) a few periodical titles account for a greater part of the total use of the periodical collection; 2) periodicals published within the last five years provide a large part of the information sought by the users; and, 3) periodical usage gradually declines with increasing age of the journals. The study was based on the analysis of cancelled periodical request/charge slips collected from July 7, 1981 through October 26, 1981.